Theological Construction of Women: Sexuality and Power in Early Marriage - Dainori Dainori; Tamimah Tamimah (International Journal of Nusantara Islam, 2026)
This study examines early marriage as a social practice constructed and sustained through patriarchal systems of knowledge. It analyzes how religious discourse, cultural traditions, and power relations legitimize early marriage as a socially accepted norm while proposing a more egalitarian reconstruction of theological knowledge. This research employs a qualitative method using a descriptive-critical approach and Michel Foucault's discourse analysis to investigate how knowledge concerning women's bodies, sexuality, morality, and marriage is produced, disseminated, and regulated through families, religious authorities, cultural leaders, and social institutions. Data were collected through a literature review of scholarly publications, legal regulations, and documented social phenomena related to early marriage. The findings demonstrate that early marriage is not merely driven by economic hardship or limited educational opportunities but is deeply embedded in patriarchal knowledge systems that reinforce unequal gender relations. Dominant discourses concerning sexual morality, family honor, female virginity, and marriage as the primary solution to moral concerns create strong social pressure on young women to marry at an early age. These narratives position women as objects of social control while legitimizing gender inequality through religious and cultural interpretations. Therefore, preventing early marriage requires more than legal reform or economic intervention. It also demands the reconstruction of theological, educational, and cultural knowledge that challenges patriarchal assumptions and promotes gender justice. Such transformation should involve families, educational institutions, religious leaders, communities, and the state in fostering egalitarian values, strengthening child protection, expanding women's autonomy, protecting human dignity, for future generations.